Pengaruh Penetapan Harga Oleh Tengkulak, Luas Lahan Dan Biaya Produksi Terhadap Pendapatan Petani Padi Di Desa Pastap Kecamatan Tambangan Kabupaten Mandailing Natal - Lubis, Nur Jannah; Arif, Muhammad; Syarvina, Wahyu (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Agriculture has an important role in life because it has the function of providing food, animal feed, and bionergy. The role of Agriculture is so strategic to support the national economy, especially in terms of creating food security, employment, increasing competitiveness, and menaggulangi poverty. Therefore, this study aims to determine the effect of pricing, land area and production costs on the income of rice farmers in Pastap Village, Kec. Mining District. Mandailing Natal. After conducting field research, data on the study were collected through the distribution of questionnaires to 67 samples of respondents. The sampling technique uses slovin formula from 200 populations into 67 samples. The research method uses quantitative methods through data analysis techniques using instrument tests, classical assumption tests and hypothesis tests. The results of data processing using SPSS 23 show that the indicators in this study are valid and reliable. In the classical assumption that the data is normally distributed, there is no heterokedasticity and multicollinearity. While the hypothesis test states that price determination does not have a significant effect on the income of rice farmers, but Price Determination is not at all unimportant, it's just that the effect is less in this study. Partially, the price fixing effect is only 1.25%. While the hypothesis test of land area and production costs to income partially positive and significant effect, partially effect of 5.12% and 53.14%. And simultaneously variable pricing, land area and production costs affect 59.5% in this study.